Hubungan Tingkat Pengetahuan Dengan Kepatuhan Penggunaan Sunscreen Pada Pengemudi Ojek Online di Kota Palangka Raya - Salenda, Rivangga; Teresa, Astrid; Widodo, Tri; Arifin, Syamsul; Trisia, Adelgrit (Barigas: Jurnal Riset Mahasiswa, 2025)
Knowledge of the Indonesian people regarding to sunscreen and awareness of its use is still low, especially among men. Online motorbike taxi riders needs to use some additional protection such as sunscreen. This study aims to find out the level of knowledge and compliance possessed by online motorbike taxi riders about sunscreen and to analyze the correlations between the two variables.This research is an analytical observational research with cross-sectional data collection using a questionnaire. The total number of participants in the research are 30 people. For the knowledge level, the majority online motorbike taxi riders are at a good level (60%) and at a low level (86.7%) for the compliance level variable. The statistical test results show that the correlations between the two variables is not significant and it is negative (p = 0.116; r = -0.293).The level of knowledge of online motorbike taxi riders in Palangka Raya City is good but compliance in their use is still low. There is no relationship between the level of knowledge and compliance with sunscreen use among online motorbike taxi riders in Palangka Raya City.